Demographic and laboratory evidence of non sexual transmission of HIV in Nigeria (2004)
Apart from heterosexual transmission, not much is known about the contribution of the other modes of spread of HIV in Africa. To evaluate the importance of non-sexual/non-vertical transmission in adults and children in Nigeria, data from mother-child pairs (community and hospital) and a community HIV surveillance among adult populations in two communities of Oyo State in SW Nigeria were analysed. In the community-based mother-child pair HIV testing, 18 of 476 (3.8%) under 5 years children were positive for HIV antibodies with only one positive mother-child pair. In the hospital surveillance (1996-1997) 10(7.0%) children of 132 mother-child pairs were positive while three (30%) of the 10 mothers were HIV negative. Similarly, 5(10%) of the mothers of 10 H1V positive children (2004) were HIV negative. In another community study, 5(13.2%) of the 38 adults from Ibadan and 12(4.8%) of 251 from Saki who claimed they never had sexual experience were HIV positive. Use of contaminated instruments and blood transfusion remain important routes of transmission of HIV in Nigeria.